Formulation of Non-effervescent Floating Dosage Form of Metronidazole using Sintering and Sublimation Technique - Ovenseri, Airemwen Collins; Michael, Uhumwangho Uwumagbe (Dhaka University Journal of Pharmaceutical Sciences, 2021)
The aim of this study was to formulate a novel non-effervescent floating dosage form of metronidazole using the sublimation and sintering technique. Granules were formulated using the wet granulation technique. Ammonium bicarbonate (30% w/w) was incorporated as the sublimating agent. The granules were characterized for micromeritic properties. Thereafter, the granules were compressed using a single punch tableting machine and the physicotechnical properties were evaluated. The metronidazole tablet was then sintered at 70oC for 12 h. All granules were free flowing and compressible. The metronidazole tablets had no floating lag time showing that tablets floated instantaneously. FTIR and DSC studies showed that metronidazole and the excipients used in the formulation were compatible. Azadirachta indica gum was used in the formulation of non-effervescent floating dosage form of metronidazole using sublimation and sintering technique which is beneficial in sustained release formulations. Dhaka Univ. J. Pharm. Sci. 20(1): 11-17, 2021 (June)